FROZEN-WEIGHT-DRAINED-WEIGHT RELATIONSHIP IN BLOCK-FROZEN SHRIMP - Rao, K Krishna; Iyer, T S Gopalakrishna (Indian Journal of Fisheries, 2011)
The nature of relationship between drained weight and frozen weight inblock-frozen shrimp wns studied with particular reference to the peeled andundeveined shrimp of small size grades. Nine sets of data were used, and regressionswere determined with frozen weight as independent variate and drainedweight as the dependent one. The slopes and intercepts of the nine regressionlines were tested for equality. While the slopes could be considered to be uniform,the intercepts showed nonuniformity